1-Nitrosos-2-naphthol and Its Position Isomer as Photometric Reagent for Copper Determination in Aqueous Phase - Kumar Singh, Vinak; Bhajan Singh, Har; Gaur, Aprajita; Lal Sharma, Rattan (Asian Journal of Chemistry, 2010)
Complexation reactions of copper(II) with 1-nitroso-2-naphthol and its position isomer 2-nitroso-1-naphthol have been studied in aqueous phase in presence of Triton X-100 and spectrophotometric methods of determining copper(II) developed. Molar absorption coefficient (∈), specific absorptivity (a), Sandell's sensitivity (S) and conditional stability constant of the two complexes at 490 nm and 505 nm (the respective absorption maxima) at pH 6.0 and 6.5 (the corresponding optimum pH) have been found to be 1.013 X 104 1 mol–1 cm–1 and 1.298 1 mol–1 cm–1; 0.159 ml g–1 cm–1 and 0.204 ml g–1 cm–1; 6.273 ng cm–1 and 4.895 ng cm–1; 5.907x 10712 mol–2 and 5.240x 107 12mol–2 respectively. Beer's law is obeyed from 4 to 24 μM and 8 to 32 μM of copper(II) respectively. Interference of common cations, anions and ligands have been investigated and the method applied successfully to determine copper content in a number of alcoholic beverages.